Study of Factors Affecting Micro-barriers that Hinders the Development of Private Enterprises: Mediating Role of Intention to Use of Renewable Energy - Cong, Phan The; Uyen, Pham Thi Minh (International Journal of Energy Economics and Policy, 2020)
Private enterprises in Vietnam as well as in other countries play an important role in the economy, but they have encountered several barriers in their development at both micro and macro levels. Inquires of these barriers is meaningful in making policy recommendations to remove barriers to private enterprise development in countries where the State/Government is considered a major factor. This study focuses on evaluating factors affecting the micro-barrier system that hinder the development of private enterprises in Vietnam to answer two research questions: which factors influence micro-barriers that hinder the development of private enterprises in Vietnam and what is the degree of influence of those factors along with the mediating impact of intention to use of renewable energy? The study applies quantitative research methods to measure the impact of factors on the micro-barriers system that hinder private enterprise development based on the survey sample of 392 private enterprises in Vietnam, which are mainly small and medium-sized private enterprises (most affected by micro barriers). Research findings indicate that state management policies; legal and tax systems, expanding scientific research and technological innovation activities are the main factors affecting the micro barriers that hinder the development of private enterprises in Vietnam. Intention to use of renewable energy significantly mediates between competitiveness in production and business, support for scientific research and technological innovation activities, expanding cooperation and international integration, state management policy, law and tax and barriers restricting enterprise development. These results could become experiences for other countries like Vietnam. Keywords: Tectonic government; Tectonic state; Innovative government; Remove barriers; Private enterprises; Renewable energy JEL Classifications: L2; O2; Q2 DOI: https://doi.org/10.32479/ijeep.10588